Activation of the periaqueductal gray controls respiratory output through a distributed brain network - Prostebby, Mitchell; Saini, Jashan; Biancardi, Vivian; Dickson, Clayton T.; Pagliardini, Silvia (Frontiers in Physiology, 2025)
IntroductionThe periaqueductal gray (PAG) has been previously established to play a key role in producing the vital changes in respiration occurring in response to threat. However, it is not fully understood how PAG activation alters the ongoing respiratory output, nor it is understood which pathways mediate these effects, as several regions have been previously identified to influence respiratory activity.MethodsWe used optogenetic tools in conjunction with EMG recordings of inspiratory and expiratory musculature to determine how PAG activation on short (250 ms) and longer (10–15 s) timescales alters respiratory muscle activity. Through cFOS mapping, we also identified key downstream brain regions which were likely modulated by PAG activation including the preBötzinger Complex (preBötC) and the lateral parafacial area (pFL). We then stimulated PAG terminals in those regions to determine whether their activity can account for the observed effects of PAG stimulation.ResultsDirectly stimulating the PAG resulted in prominent changes to all recorded muscle activities and reset the breathing rhythm in either a phase-independent or phase-dependent manner. In contrast, stimulating PAG terminals in either preBötC or pFL with long or shorter timescale stimuli could not completely replicate the effects of direct PAG stimulation and also did not produce any respiratory reset.ConclusionsOur results show that the effects of PAG activity on respiration are not mediated solely by PAG inputs to either the preBötC or pFL and more likely involve integration across a larger network of brainstem areas.